The Creation of Adam and Eve in the Bible and the Qur’an: A Comparative Analysis of Its Theological Implications - Norakmal binti Abdul Hamid, Wan Sabri bin Wan Yusof (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Creation of Adam and Eve in the Bible and the Qur’an: A Comparative Analysis of Its Theological Implications